A randomized study of comparison of intravenous dexmedetomidine and intravenous esmolol to attenuate the cardiovascular responses to laryngoscopy and endotracheal intubation - Chodankar, Ninad Deepak; Shivde, Bhagyashree (International Journal of Research in Medical Sciences, 2020)
Background: The objective of this study was to compare the efficacy of intravenous dexmedetomidine and esmolol in attenuating the cardiovascular pressor responses to laryngoscopy and endotracheal intubation. Method: Study was done on 60 adults, American society of anesthesiologists (ASA) grade I or II normotensive patients, undergoing elective surgery under general anesthesia and willing to participate. These patients were randomly allocated to either group E (esmolol) or D (dexmedetomidine). Group ‘D’, patients were given intravenous dexmedetomidine infusion 1 mcg/kg over 10 minutes, 3 minutes before start of laryngoscopy. Group ‘E’, patients were given intravenous esmolol 1.5 mg/kg 2 minutes before start of laryngoscopy. All patients were premedicated, induced and intubated using thiopentone and succinyl choline as per the protocol. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were recorded at baseline (taken half an hour prior to anesthesia), before sedation, after induction but before intubation, immediately after endotracheal intubation and thereafter at 1, 2, 3, 4, 5 and 10 minutes. Results: Immediately after intubation, HR was similar in group D and group E, thereafter HR remained higher in group E as compared to group D, and difference was statistically significant. SBP, DBP and MAP recorded was higher in group E as compared to group D, and difference was statistically significant. Conclusion: Authors conclude that intravenous dexmedetomidine 1 ug/kg is better drug to attenuate hemodynamic response to laryngoscopy and intubation as compared to intravenous esmolol 1.5 mg/kg.